Framing of climate change in South Africa: An analysis of content in News24 and TikTok - Mawila, Cathrine (University of the Witwatersrand, Johannesburg, 2024)
Climate change has become a danger to the planet and human survival. This has incited dialogs about the subject to gain momentum on international economic and political platforms. The discussion about climate science and climate change is mainly conducted in the mainstream media and the internet. However, the internet, as a communication channel, is fast taking over the role of traditional media as a platform for distributing information to the public. The internet has opened up new avenues for public debates and has allowed the public to discuss important issues such as climate change. In South Africa, many researchers employed the content analysis media theory to study different frames on news media coverage of climate change. Previous studies analysed tweets and blogs in South Africa on the subject of climate change and argued that although there was some closeness in the way print media and online media covered topics on climate change, online media had become the most frequently used to interact and reach audiences effectively and in real-time. This study took the matter forward and compared the framing of climate change in two distinct platforms, News24 and TikTok, between April 2022 and April 2023 to understand the topic across diverse sections of media users in South Africa. The study found that News24's framing of climate change was mostly linked to weather events or climate disasters, while TikTok's engagement with the issue was found to be inadequate. The study also found that misinformation was prevalent in TikTok. Furthermore, News24's articles were influenced by international narratives, while TikTok's frames were based on rudimentary knowledge. The most prevalent frames in both News24 and TikTok were socio-economic and disaster-related, likely due to the recent KZN floods. The study also found that TikTok lacks reputable sources. The findings of this study could prove useful in guiding climate change communicators to focus on educating the general public about climate change, given the prevalence of climate change misinformation on social media platforms
A research report Submitted in fulfillment of the requirements for a Master of Arts in journalism and media studies, In the Faculty of Humanities , School of Social Sciences, University of the Witwatersrand, Johannesburg, 2024
Keywords: SDG-13: Climate action